Cardiovascular impact of testosterone therapy for hypogonadism. (2nd September 2018) - Rastrelli, Giulia; Dicuio, Mauro; Reismann, Yacov; Sforza, Alessandra; Maggi, Mario; Corona, Giovanni
ABSTRACT: Introduction : Since 2010 some evidence supporting the possible increased cardiovascular (CV) risk related to testosterone treatment (TTh) has created much debate in the scientific community. Based on these results, the US Food and Drug Administration agency has questioned TTh for aging men recognizing its value only for classical hypogonadism due to genetic or organic causes. To better clarify this topic, we scrutinized and summarized, also by using meta-analytic methods, the data generated during the last 7 years, as derived from the analysis of randomized controlled trials (RCTs) on TTh and CV risk. Areas covered : Analysis included 31 RCTs published between 2010 and 2018. Retrieved trials included 2675 and 2308 patients in TTh and placebo groups, respectively. The analysis documented that TTh was not associated with an increased CV mortality or morbidity either when overall or major adverse CV events were considered. Expert commentary : Despite present evidence it is important to recognize that the duration of the available trials is short (lower that 3 years) limiting final conclusions on this topic. In particular, the available information on possible long-term effects of TTh on CV risk is limited. Long-term safety studies are advisable to better clarify these points.